On Geometric Characteristics of an n-Dimensional Simplex - M. V. Nevskii (Моделирование и анализ информационных систем)
We prove and discuss some propositions for geometric characteristics of an n-dimensional simplex. Also we note the connection with linear interpolation on the cube [0; 1]^n.